Judicial Transformation: Integration of AI Judges in Innovating Indonesia's Criminal Justice System - Panca Sarjana Putra; Zico Junius Fernando; Bhanu Prakash Nunna; Rizaldy Anggriawan (Universitas Muhammadiyah Purwokerto, 2023)
In the midst of the current digital era, artificial intelligence (AI) technology offers the potential to improve many aspects of life, including in the field of justice. In this context, the idea of integrating AI into the judicial system emerges as one potential solution. AI judges, as a concept, are considered capable of providing more objective decisions, speeding up court proceedings, and reducing the workload of human judges. The purpose of this study is to evaluate the potential and challenges in the integration of artificial intelligence (AI) into the Indonesian judicial system, with the ultimate goal of creating a judicial system that is more fair, efficient, and in accordance with Indonesia's socio-cultural context. This research utilizes normative legal methods by adopting statutory, conceptual, comparative, and futuristic approaches. The nature of this research is descriptive-prescriptive. The data that has been collected is analyzed using the content analysis method. The result of this research is that